Regulating regulators in transitionally competitive markets - Sappington, David E. M.; Weisman, Dennis L. (My University, 2012)
During the course of the first thirty CRRI conferences, we have gained considerable insight about how to design regulatory policy in the presence of developing competition. The insight to date has focused on how to harness competitive forces to motivate incumbent suppliers to serve the best interests of consumers. This paper stresses the importance of considering the incentives of regulators and explores the associated changes in standard recommendations for regulatory policy design in the presence of developing competition.
Keywords: Regulatory policy; Regulating regulators; Regulation and competition